A New Approach for The Automation of Spatial Data Updates Using ArcGIS ModelBuilder for Provincial Planning in The Region of Nghe An, Vietnam - Le, Thi Minh Phuong; Bui, Hai Phong (International Journal of Sustainable Construction Engineering and Technology, 2025)
Timely updating of administrative boundaries in national spatial databases is a critical component of modern territorial management, especially in the context of administrative restructuring in many countries. Traditional updating methods in ArcGIS remain largely manual, involving multiple discrete steps that are time-consuming and error-prone. This study proposes a semi-automated spatial data updating model using ModelBuilder within the ArcGIS environment to streamline the process into a single workflow. A case study was conducted in Nghe An province, Vietnam, which is undergoing commune-level administrative mergers. The proposed model reduced processing time by 70% while maintaining spatial accuracy in compliance with the VN-2000 coordinate system and current technical standards. The study has processed a large amount of spatial data that was collected from 2010 to 2024 in Nghe An province, Vietnam. The model was further piloted in three additional provinces and a regional planning project involving 14 northern midland and mountainous provinces, demonstrating its scalability and potential for integration into national and subnational planning databases. This approach provides a replicable solution for other countries facing similar administrative restructuring, supporting efficient and accurate spatial data management. The model also directly supports the integrated provincial planning process for the 2021–2030 period and beyond.